Evaluation of real-time qPCR-based methods to detect the DNA of the three protozoan parasites Cryptosporidium parvum, Giardia duodenalis and Toxoplasma gondii in the tissue and hemolymph of blue mussels (M. edulis). (April 2022) - Cazeaux, Catherine; Lalle, Marco; Durand, Loïc; Aubert, Dominique; Favennec, Loïc; Dubey, Jitender P.; Geffard, Alain; Villena, Isabelle; La Carbona, Stéphanie
Abstract: The protozoan parasites Cryptosporidium spp., Giardia duodenalis and Toxoplasma gondii can be transmitted to humans through shellfish consumption. No standardized methods are available for their detection in these foods, and the performance of the applied methods are rarely described in occurrence studies. Through spiking experiments, we characterized different performance criteria (e.g. sensitivity, estimated limit of detection (eLD95METH ), parasite DNA recovery rates (DNA-RR)) of real-time qPCR based-methods for the detection of the three protozoa in mussel's tissues and hemolymph. Digestion of mussels tissues by trypsin instead of pepsin and the use of large buffer volumes was the most efficient for processing 50g-sample. Trypsin digestion followed by lipids removal and DNA extraction by thermal shocks and a BOOM-based technique performed poorly (e.g. eLD95METH from 30 to >3000 parasites/g). But trypsin digestion and direct DNA extraction by bead-beating and FastPrep homogenizer achieved higher performance (e.g. eLD95METH : 4–400 parasites/g, DNA-RR: 19–80%). Direct DNA recovery from concentrated hemolymph, by thermal shocks and cell lysis products removal was not efficient to sensitively detect the protozoa (e.g. eLD95METH : 10–1000 parasites/ml, DNA-RR ≤ 24%). The bead-beating DNA extraction based method is a rapid and simple approach to sensitively detect the three protozoa in mussels using tissues, that can be standardized to different food matrices. However, quantification in mussels remains an issue. Highlights: Cryptosporidium, Giardia & Toxoplasma can be transmitted to humans via mussels. A standardized method is required to detect the three parasites by qPCR. Trypsin & large buffer volumes improve qPCR detection in mussel's tissues. Bead-beating & FastPrep homogenizer are efficient for parasite DNA extraction from tissues. Hemolymph analyzed by direct DNA recovery is not relevant for environmental studies.